How can the Student Portfolio Help Improve Teaching Practices? - Orbea-Aizpitarte, Goretti (2019)
The purpose of this work was to inquire into the aspects that college students consider as significant of the faculty collected in the portfolios so that, in the light of this exploration, the faculty can reflect on their teaching practices and put forward proposals for improvement and change. It is proposed as qualitative research where the case is the analysis of student portfolios of the Management of Specific Projects course of the Interculturality Module (Minorkult). The tool being studied, also the main strategy for the generation of data, was the student portfolio and the analytical procedure consisted of a hermeneutic analysis of thematic contents. As a result, it is worth noting that, by opting for the portfolio, the faculty has strengthened the voice and visibility of the students, as well as their autonomy in the learning process, and has generated reflective processes within the faculty aimed at improving their teaching practice.